2016
DOI: 10.1682/jrrd.2014.12.0311
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanical response of persons with transfemoral amputation to variations in prosthetic knee alignment during level walking

Abstract: Prosthetic alignment is an important factor in the overall fit and performance of a lower-limb prosthesis. However, the association between prosthetic alignment and control strategies used by persons with transfemoral amputation to coordinate the movement of a passive prosthetic knee is poorly understood. This study investigated the biomechanical response of persons with transfemoral amputation to systematic perturbations in knee joint alignment during a level walking task. Quantitative gait data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 45 publications
(55 reference statements)
1
15
0
Order By: Relevance
“…For the prosthesis user, the standard deviations of joint angles and joint torques were greater than those of the subject with intact legs (AB04). The standard deviation of the vertical GRF is similar for both the prosthesis user and the subject with intact legs, but the average vertical GRF of the subject with intact legs is greater than that of the prosthesis user, which agrees with previous observations that prosthesis users place more weight on their intact side than on their prosthesis Koehler-McNicholas et al [ 26 ]. That is, the maximum vertical GRF in the mid-stance phase is 930 N for the subject with intact limbs, but only 815 N for the transfemoral prosthesis user.…”
Section: Discussionsupporting
confidence: 90%
“…For the prosthesis user, the standard deviations of joint angles and joint torques were greater than those of the subject with intact legs (AB04). The standard deviation of the vertical GRF is similar for both the prosthesis user and the subject with intact legs, but the average vertical GRF of the subject with intact legs is greater than that of the prosthesis user, which agrees with previous observations that prosthesis users place more weight on their intact side than on their prosthesis Koehler-McNicholas et al [ 26 ]. That is, the maximum vertical GRF in the mid-stance phase is 930 N for the subject with intact limbs, but only 815 N for the transfemoral prosthesis user.…”
Section: Discussionsupporting
confidence: 90%
“…Prosthetic alignment next to functioning of the prosthetic knee joint has a significant influence on the biomechanical performance of a prosthesis [33,34]. In order to attribute functional differences of the knee joints exclusively to their properties, an identical prosthetic alignment is mandatory for comparative biomechanical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Schmalz et al [25] verified that an increased energy expenditure is required in case of a wrong alignment and this effect results more significant for transfemoral amputees, than for transtibial ones. Furthermore, it has been found that a wrong alignment in transfemoral amputees, causes an increased hip extension moment during the early stance phase, trunk flexion, a decreased step length and other undesired biomechanical effects [37].…”
Section: A Biomechanical Parameters In Lower Limb Amputeesmentioning
confidence: 99%